Social Self-Efficacy and Internet Gaming Disorder Among Chinese Undergraduates: The Mediating Role of Alexithymia and the Moderating Role of Empathy - Zhang, Yanhong; Liang, Ting; Gan, Xiong; Zheng, Xueyan; Li, Hao; Zhang, Jingyue (Frontiers in Psychology, 2022)
As an increasingly serious social problem, Internet gaming disorder (IGD) of college students may be related to their social self-efficacy. However, the relationship and its internal mechanisms underlying are still unclear. The current study tested the mediating effect of alexithymia in the association between social self-efficacy and IGD, and whether this mediating process was moderated by empathy. Social Self-Efficacy Scale (PSSE), Chinese version of Internet Game Addiction Scale (IGAS-C), Toronto Alexithymia Scale (TAS-20) and Interpersonal Response Scale (IRI-C) were adopted to examine the model on 888 Chinese college students. The results indicated that social self-efficacy was significantly negatively associate with IGD. Mediation analysis illustrated that alexithymia mediated the association between social self-efficacy and IGD. Further, moderated mediation analysis manifested that the mediated effects was stronger for lower level of empathy. The conclusions corroborate and clarify the mechanisms that alexithymia mediated the association between social self-efficacy and IGD, and the mediation effects is moderated via empathy. Besides, these findings provide available references for colleges to conduct educational activities, and at the same time provide scientific suggestions for preventing IGD among undergraduates.